PHOTOMETRIC OBSERVATIONS OF AG PEGASI - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
We have made UBVJHKL broad-band photometry, and H_ß and H_d narrow-band photometry of the symbiotic star AG Pegasi. The ß and d-indices for this object are the strongest among nearly 200 Be stars (which include P Cygni) and standard stars. The UBV photome
BOL OBS TONAN TACUB
Keywords: PHOTOMETRIC, OBSERVATIONS, PEGASI; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA